Budget support as more effective aid? : recent experiences and emerging lessons - Koeberle, Stefan; Stavreski, Zoran; Walliser, Jan.; Strategic Partnership with Africa (Washington, D.C. : World Bank, 2006)
Presents a review of key concepts, issues, experiences and emerging lessons relevant to budget support. This book is useful for practitioners in aid-recipient countries and international financial institutions, bilateral agencies and civil organizations involved in budget support
Contributions discussed at the Practioners' Forum on Budget Support in May 2005 in Cape Town, South Africa, along with conclusions from a May 2005 workshop conducted by the Budget Support Working Group of the Strategic Partnership with Africa (SPA).
Includes bibliographical references (p. 479-494) and index.
lje 18/07/2016
Loans
Keywords: Economic assistance; Budget; Economic development